2007
DOI: 10.1002/mde.1320
|View full text |Cite
|
Sign up to set email alerts
|

Organisational susceptibility to fraud and theft, organizational size and the effectiveness of management controls: some UK evidence

Abstract: This paper examines the principal determinants of an organization's susceptibility to theft and fraud in the context of a rational economic framework in which the level of protection is determined by the minimization of cost. The empirical study shows that, adjusting for differences in organizational type and industrial sector, both organizational susceptibility and the size of a typical theft or fraud increase with organizational size. Access to resources and the manner in which the theft or fraud is perpetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, large organizational size was also positively associated with the odds of reporting the occurrence of occupational fraud at a one percent confidence level (p < 0.01). A study by Barnes and Webb (2007) similarly found that the vulnerability to internal fraud increased the greater the size of an organization. This can be explained in terms of Routine Activity Theory (Felson, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, large organizational size was also positively associated with the odds of reporting the occurrence of occupational fraud at a one percent confidence level (p < 0.01). A study by Barnes and Webb (2007) similarly found that the vulnerability to internal fraud increased the greater the size of an organization. This can be explained in terms of Routine Activity Theory (Felson, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In small companies, there is a lack of separation of duties, and control action is vital to avert fraud. The findings of Barnes and Webb (2007) revealed that company size impacts the vulnerability to fraud and the subsequent harms.…”
Section: Research Hypothesis Developmentmentioning
confidence: 99%
“…According to Singleton et al [47], size is reflected in the following points: (i) fraudulent financial reporting is more likely to occur in large organizations, whereas misappropriation of assets occurs more in small organizations; (ii) large organizations have more resources to improve internal control and invest in internal audit and fraud prevention and detection programs; and (iii) segregation of duties is insufficient or absent in smaller organizations, and this control activity is relevant to preventing fraud. Barnes and Webb [81] found that susceptibility to fraud and the resulting losses are affected by organizational size.…”
Section: Hypothesis Developmentmentioning
confidence: 99%